Promoting Language and Scientific Literacy Through Children's Literature: A Systematic Literature Review - Heryani, Rina; Muyassaroh, Izzah; Heryanto, Dwi; Somantri, Mubarok; Mulyasari, Effy; Rakhmawati, Evi; Salimi, Moh. (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
ABSTRACTChildren's literature is widely recognized for its potential to enhance student development. Despite existing research and publications on the topic, a thorough study on integrating children's literature into language and scientific literacy has not been widely conducted. This systematic literature review aimed to comprehensively explore current literature on innovative strategies and the effects of integrating children's literature to improve language and scientific literacy. Utilizing the Systematic Literature Review (SLR) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methods, this review analyzed 54 studies from the Scopus database spanning 2010 to 2024. The Publish or Perish and VOSviewer applications supported the identification, screening, eligibility, and inclusion stages. Scopus-indexed articles totaling 275 were initially identified and filtered into 54 relevant pieces. The findings highlight that integrating children's literature into science education effectively bridges language and scientific literacy, enhancing cognitive development and comprehension. The potential of this interdisciplinary teaching model suggests practical applications for educators seeking to enrich their instructional strategies by employing diverse literary forms such as informational texts, biographies, comics, dramas, and science fiction. Ultimately, this review emphasizes children’s literature's significant role in advancing language and scientific literacy in educational contexts. Keywords: children’s literature, language literacy, scientific literacy